The Efektivitas Model PBL Berbantuan Aplikasi Qreatif Terhadap Berpikir Kritis dan Motivasi Pembelajaran IPA SD - Diyanti, Siti Khodijah; Utama, Candra; Estu Winahyu, Sri (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
The lack of variation in learning models and media makes it difficult for students to focus, think critically, and feel motivated in science learning activities. This study aims to determine whether the Problem-Based Learning (PBL) model assisted by the Qreatif application is effective in improving critical thinking skills and learning motivation among fourth-grade students in science lessons at SDN Panggungrejo, Pasuruan City. A quantitative approach with a quasi-experimental design and control group was used. Data were collected using a critical thinking skills test and a learning motivation questionnaire. The results of the t-test showed a significance value of < 0.001 (p < 0.05), indicating a significant difference between the experimental and control classes. Therefore, the PBL model supported by the Qreatif application was proven to be more effective than conventional models in enhancing students’ critical thinking skills and motivation in learning science.